Dynamic loading on flexible floating anticollision system due to head-on collision by uncontrolled vessel - Sun, Zhenxiang (2020)
The design of flexible floating anticollision systems (FFAS) against collision by uncontrolled vessels is based on quasi-static considerations, in which the maximum loading is taken to occur when the vessel is brought to a standstill and its kinetic energy is completely transferred to the strain and frictional energy of FFAS. The dynamic loading during the collision process due to system response characteristics of the FFAS is typically ignored. In the present study, the authors demonstrated through an experimental investigation that it is critical to consider both quasi-static and dynamic loadings to design against possible failures of the system. The experimental investigation was performed as a case study for a FFAS to protect a chemical wharf at Zhangzhou Port, China. The system consisted of a row of floating buoys connecting and mooring with steel chains. Extensive physical modeling tests were performed to quantify the motion of the collided buoy and the tensions of selected block and mooring chains when the FFAS was struck by a 5,000-DWT(deadweight tonnage) vesselmodel with different initial velocities. The results showed that the transient impact force on the system had multiple dynamic peaks during the collision process. Most importantly, the maximum loading on the FFAS (and the reaction impact force on the vessel in the opposite direction) occurred at a dynamic peak prior to when the vessel was halted to a standstill, and the magnitude was larger than the maximum quasi-static loading based on energy transfer principle alone. Thus, the case study highlighted the importance of including the dynamic loading and responses into the design considerations of FFAS.